Seroepidemiology of human toxocariasis in selected population groups in Slovakia: A cross-sectional study - Miroslava Fecková; Daniela Antolová; Grzegorz Zaleśny; Monika Halánová; Gabriela Štrkolcová; Mária Goldová; Tatiana Weissová; Branislav Lukáč; Mária Nováková (Elsevier, 2020)
Background: Human toxocariasis is a cosmopolitan helminthic zoonosis caused by roundworms of the genus Toxocara. The study aimed at a cross-sectional analysis of seropositivity to Toxocara spp. in selected groups of population in Slovakia and an estimate of the risk factors of infection. Methods: For the detection of anti-Toxocara antibodies, an enzyme-linked immunosorbent assay (ELISA) based on an excretory-secretory (E/S) antigen of Toxocara canis was used. Results: The overall seropositivity to Toxocara in 1489 evaluated sera was 3.7%. The seropositivity of Roma children/young people (40.3%) was significantly higher when compared with all other analysed groups. Among adult respondents, the positivity of farmers and hunters (5.5% and 5.1%, respectively) was significantly higher (p < 0.001) than in the other analysed groups (veterinarians and veterinary assistants, soldiers, students of veterinary medicine, and students of other universities). Analysis of infection risk factors showed that living in a rural locality, everyday contact with soil, and everyday outdoor activities (12.7%, 8.8% and 8.3% positivity, respectively) can increase the risk of infection, but the observed differences were not significant. Conclusion: The results underline the importance of preventive measures and the need for improving of knowledge of toxocariasis among professionals, as well as the public.